2002
DOI: 10.1074/jbc.m201941200
|View full text |Cite
|
Sign up to set email alerts
|

The Serine Protease Plasmin Triggers Expression of MCP-1 and CD40 in Human Primary Monocytes via Activation of p38 MAPK and Janus Kinase (JAK)/STAT Signaling Pathways

Abstract: The mechanism of proinflammatory activation of human monocytes by plasmin is unknown. Here we demonstrate that in human primary monocytes, plasmin stimulates mitogen-activated protein kinase (MAPK) signaling via phosphorylation of MAPK kinase 3/6 (MKK3/6) and p38 MAPK that triggers subsequent DNA binding of transcription factor activator protein-1 (AP-1). The AP-1 complex contained phosphorylated c-Jun and ATF2, and its DNA binding activity was blocked by the p38 MAPK inhibitor SB203580. In addition, plasmin e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
148
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 151 publications
(152 citation statements)
references
References 75 publications
3
148
1
Order By: Relevance
“…The lesser MCP-1 production might be due to the lower phosphorylation of Stat family proteins in IL-34-macrophages (Figure 4b), as the activation of Stat was required for the expression of MCP-1. 27,28 Given that chemokines have a crucial role in immune and inflammatory reactions 29 and thus their expression should be tightly regulated, 30 our result implies that IL-34 and M-CSF are differently involved in those reactions. Using cultured cell lines, we further showed that IL-34 and M-CSF differently regulated cellular phenotypes.…”
Section: Discussionmentioning
confidence: 91%
“…The lesser MCP-1 production might be due to the lower phosphorylation of Stat family proteins in IL-34-macrophages (Figure 4b), as the activation of Stat was required for the expression of MCP-1. 27,28 Given that chemokines have a crucial role in immune and inflammatory reactions 29 and thus their expression should be tightly regulated, 30 our result implies that IL-34 and M-CSF are differently involved in those reactions. Using cultured cell lines, we further showed that IL-34 and M-CSF differently regulated cellular phenotypes.…”
Section: Discussionmentioning
confidence: 91%
“…Leptin was used at concentrations of 25-100 ng/ml. The inhibitors and their concentrations were: 50 M JAK inhibitor AG 490 (45)(46)(47); 1000 units/ml catalase (49); 20 M p38 inhibitor SB203580 (39,48); 20 M SB202474 (an inactive analog of SB203580) (52); and 30 M ERK1/2 inhibitor PDO98059 (39,50). Me 2 SO was used as vehicle control for the inhibitors.…”
Section: Methodsmentioning
confidence: 99%
“…In vitro, plasmin can activate proinflammatory signaling networks, which leads to the phosphorylation and activation of p38 MAPK and JAK/STAT signaling pathways and eventually to the induction of cytokines and tissue factors in macrophages (15). Recent studies in glomerular mesangial cells have shown that uPA mediates a proinflammatory effect via the Tyk-2/STAT-3 pathway (16).…”
mentioning
confidence: 99%